PERAN MUSEUM TANI JAWA INDONESIA DALAM PENINGKATAN KINERJA DESA WISATA CANDRAN BANTUL - Wahyuno, Hardi (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2015)
Since the tourist arrive at location as rural market palce, they will get soon their gaze, as they watch some products. These products include location, price, service, facilities, images, in the dynamic of developement of the local people.The local people is considered to be supplier of the product, as seen in the tourisme point of view. The basic point of view of the tourist is the romantisme and nostalgia is experienced at location and it’s relation with the tourist capacity and capability to understand some associations of the products, as products are categorized and branded, under neath they are the controled as well as the tourist understand the meaning of the symbols localy, in the form of cultural goods. This case raise up some tourismes consideration which this will be studied in the field of comparative rural tourisme, heritage tourisme. The tourists have their own criteria in understanding people ‘s way of life, developement, condition, in their locality and in the other hands is the people, the way they understand the tourists’s need and wants. The relation beetwen local people and tourists attitude is in this contact, communicates the on going matter of tourisme. The attitude of the local people in the tourist village in Candran, they are the creator of their heritage. The heritage has the role for them, because of it’s value, in several degree, is coorelatively connected with local history, culture, and nature. This is important to understand the local heritage tourisme. Diversity of the dynamic rtelation between the village and the city in the tourisme context is significant and it’s difference is understood. The village, it’s self, in the tourisme context, stengthens the destination of Jogjakarta by producing the tourist village in the setting of rural tourisme, heritage tourisme. Tourist needs and wants of the rural as product (tangible-intangible) to consume , the local people make some supplies as attraction, acces includes catergorical and brand, where the product : tourist village is typical and specific, valueable, increases the power of attraction , because of it’s content, where people respons to challenge in their locality at location. The location (historicval, cultural, natural aspect) can increase tourist’s motivation, inisiate the pulled factor, and forme the heritage tourisme, rural tourisme. The role of the people, in their every day life, is as induvidual or collective local actor, they do, they create heritage for them, they expresse visually, in their attitude toward tourist (performence), as well as their attitude is focused at the rural museum. The people acts as cultural model, otentic, fixing up the proses of consumption (economics). The product to consume is attached with it’s association and it’s symbolic meaning (cultural). The Museum Tani Jawa Indonesia in Candran increase the selling value of it’s locality and try to fit with the standard expectation toward the global standar as this is the matter of the field in the comparative rural, heritage tourisme. Kata Kunci : Museum Tani Jawa Indonesia, Local Actor, Heritage, Rural Tourism, Performance